Study guides

Q: Factor the following polynomials 2a2 - 5a plus 3?

Write your answer...

Submit

Related questions

The other factor is 1.

Multiply the first and last coefficients.2*3=6What two factors give you six but when combined give you -5-2 and -3Therefore2x-3)(x-1) will be the factored model.

a(2a + 1)

(2a - 1)(a - 5)

2(a + 7)(a - 6)

What is The simplified form of (3a2 - 5ab plus c2) plus (-2a2 plus 10ab plus 6c2)

3a4 - 2a2 + 5a - 10 - 2a4 + 4a2 + 5a - 2 = a4 + 2a2 + 10a - 12 = a4 + (2a - 2)(a + 6)

a2(2a2-21a+49) a2(2a-7)(a-7)

2a2 - 13a + 15 = (2a - 3) (a - 5)

a2 + a2 = 2a2

(a - 1)(2a - 3)

5a4 + 3a3 + 2a2

(a - 2)(a^2 + 4)

a3 - 2a2 + 4a - 8 = a2(a - 2) + 4(a - 2) = (a - 2)(a2 + 4)

(a2 + a + a2) = (2a2 + a) = a (2a + 1)

First you can factor a^2 from the first two terms and 4 from the last two terms. (a^2)(a-2)+4(a-2) You can see that they both have (a-2) as a factor. So it is (a^2+4)(a-2)

2a2+3a2 = 5a2

8

5a3-45a=-2a2+18 5a(a2-9)=-2(a2-9) 5a=-2 a=-2/5

It is a quadratic expression which can't be factored because its discriminant is less than zero.

2a2

2a2+2a2 = 4a2

sqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*asqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*asqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*asqrt(a2 + a2) = sqrt(2a2) = sqrt(2)*sqrt(a2) = sqrt(2)*a

If I've read your question correctly, you need to subtract: a2 +2a -7 a2 -4a2 +5a2 -6 = 2a2 -6 Note, if x - y = z, then y = x - z; so: 2a2 -6 - (a2 -2a +1) = 2a2 -6 - a2 +2a -1 = a2 +2a -7

2a2+33a+136 = (2a+17)(a+8) when factored